Teachers self-perceived multicultural competence and their experience of culturally loaden value-based tensions in Senior Secondary Vocational Education - Tielman, K.; Wesselink, R.; den Brok, P.; Hirzalla, F. (Pedagogische Studiën, 2022)
During the last decades there has been an enormous increase in the number of students with different cultural backgrounds in schools in The Netherlands, as in many Western countries. School teachers are required to have the competences to handle such cultural differences. The present study collected data on these variables via a self-report questionnaire administered to teachers of culturally diverse Senior Secondary Vocational Education and Training (SSVET) schools. In total, 898 teachers from 20 SSVET schools completed the survey. Teachers experienced tensions from relatively limited to fairly frequent. Regarding their competencies, teachers attributed themselves a positive attitude towards multicultural education, perceived to have some degree of multicultural teaching skills and perceived their degree of multicultural education knowledge neutral. Teachers’ self-perceived multicultural knowledge, attitudes and skills had varied associations with the different experienced value-based tensions. Whereas the degree of self-perceived skill showed a positive relationship with most experienced tensions, attitudes and knowledge showed a negative relationship. These results suggest that perceiving to have more skills leads to experiencing more tensions. [...]